China's Development-Security in Practice: The Case of Mali - Lina Benabdallah; Daniel Large (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2020)
In June 2020, the United Nations renewed its Mission in Mali (MINUSMA) for another year in the midst of a complicated political crisis and increasing levels of violence. Later in the summer, a military mutiny that escalated into a coup ousted Malian President Ibrahim Boubacar Keita on August 18, further changing the already complex political landscape in Mali. This publication by Lina Benabdallah and Daniel Large sheds light on China's role and influence in Mali. The paper examines China's development-security nexus, a defining element of Chinese foreign policy in Africa, in Mali. China's development-focused approach to security in Mali has notable advantages but is also marked by serious limitations, notably around the politics of Mali's conflicts. Read on to see how in the context of Beijing's ambition to play a bigger role in Mali, and in the Sahel more broadly, the applied relationship between its developmental and security engagements are set to become more important.
Keywords: 330